2018
DOI: 10.3390/ma11091520
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of Platinum Nanoparticles into MoS2 Nanoflakes for Enhanced Hydrogen Evolution Reaction

Abstract: Pt as a chemical inert metal has been widely applied as the counter electrode in various electrochemical measurements. However, it can also be dissolved and redeposit to the working electrode under certain electrochemical circumstances. Herein we demonstrated a cyclic voltammetry (CV) cycling method to synthesize a catalyst comprising inserted Pt nanoparticles into MoS2 nanoflake stack structures on stainless steel mesh (SSM). The binder-free composite structure exhibits significantly enhanced hydrogen evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The values for η (measured at 10 mA cm À 2 ) and the Tafel slope for the PdPt/MoS 2-x @4k catalyst prepared in this study surpassed the performance of previously reported MoS 2 and PGM based catalysts (Figure 4c). [7,[10][11][12][23][24][25][26][27][28][29][30][31] The higher HER activity of the PdPt/MoS 2-x @4k catalyst in comparison to the previously reported Pt-based and Pd-based MoS 2 catalysts signifies the importance of the methods used for exfoliation, desulfurization, and metal deposition to create catalysts that are stabilized by vacancies in the support material that also help promote an efficient transport and transformation of SO 4 for the series of electrocatalysts that were each supported on separate glassy carbon, working electrodes and rotated at 1600 rpm. These plots were used to determine the onset potentials for each sample towards the HER, as well as the overpotential for each catalyst at 10 mA cm À 2 .…”
Section: Creation and Activity Of Pd And Pt Electrodeposited On Mos 2...mentioning
confidence: 99%
See 2 more Smart Citations
“…The values for η (measured at 10 mA cm À 2 ) and the Tafel slope for the PdPt/MoS 2-x @4k catalyst prepared in this study surpassed the performance of previously reported MoS 2 and PGM based catalysts (Figure 4c). [7,[10][11][12][23][24][25][26][27][28][29][30][31] The higher HER activity of the PdPt/MoS 2-x @4k catalyst in comparison to the previously reported Pt-based and Pd-based MoS 2 catalysts signifies the importance of the methods used for exfoliation, desulfurization, and metal deposition to create catalysts that are stabilized by vacancies in the support material that also help promote an efficient transport and transformation of SO 4 for the series of electrocatalysts that were each supported on separate glassy carbon, working electrodes and rotated at 1600 rpm. These plots were used to determine the onset potentials for each sample towards the HER, as well as the overpotential for each catalyst at 10 mA cm À 2 .…”
Section: Creation and Activity Of Pd And Pt Electrodeposited On Mos 2...mentioning
confidence: 99%
“…(b) Tafel plots, derived from the series of LSV plots in (a), for each of the catalysts. (c) A comparison of the HER activity as assessed using the Tafel slopes (mV dec À 1 ) versus the overpotential at a current density of 10 mA cm À 2 for a series of MoS 2 supported electrocatalysts, [7,[10][11][12][23][24][25][26][27][28][29][30][31] a commercial carbon supported Pt nanocatalyst (comm. Pt/C), and the results of the PdPt/MoS 2-x @4k sample prepared in this study.…”
Section: Creation and Activity Of Pd And Pt Electrodeposited On Mos 2...mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the diversity, stability and theoretically high catalytic activity of transition metals, recent research has focused on transitionmetal-based electrocatalysts. [29][30][31] It has been shown that nickel sulfide, 32,33 especially its composites with other metal sulfides, has superior UOR properties. For example, Liu et al prepared catalysts with efficient UOR catalytic activity via in situ growth of multistage nickel sulfide composites on nickel foam with a potential of only 1.343 V at a current density of 10 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…The main strategy in a noncovalent method is in situ synthesis of metal nanoparticles/MoS 2 hybrids in which metal nanoparticles are synthesized in the presence of MoS 2 sheets . This is a straightforward and efficient strategy in which metal nanoparticles are nucleated and then attached onto MoS 2 sheets. For example, gold nanoparticles or their core@shell structures have been incorporated onto MoS 2 sheets by sulfur/noble-metal binding to raise the effective gate voltage or to induce a catalytic effect. , A higher density of gold nanoparticles has been found in defect sites and edges of MoS 2 sheets . MoS 2 /gold nanoparticles constructed by this method have been used as efficient electrochemical sensors …”
Section: Introductionmentioning
confidence: 99%